Genera of phytopathogenic fungi: GOPHY 2 - Y. Marin-Felix (2018)
© 2018 Westerdijk Fungal Biodiversity Institute This paper represents the second contribution in the Genera of Phytopathogenic Fungi (GOPHY) series. The series provides morphological descriptions and information regarding the pathology, distribution, hosts and disease symptoms for the treated genera. In addition, primary and secondary DNA barcodes for the currently accepted species are included. This second paper in the GOPHY series treats 20 genera of phytopathogenic fungi and their relatives including: Allantophomopsiella, Apoharknessia, Cylindrocladiella, Diaporthe, Dichotomophthora, Gaeumannomyces, Harknessia, Huntiella, Macgarvieomyces, Metulocladosporiella, Microdochium, Oculimacula, Paraphoma, Phaeoacremonium, Phyllosticta, Proxypiricularia, Pyricularia, Stenocarpella, Utrechtiana and Wojnowiciella. This study includes the new genus Pyriculariomyces, 20 new species, five new combinations, and six typifications for older names.